Introduction: the new EU FTAs as contentious market regulation. Issue 7 (10th November 2017) - Laursen, Finn; Roederer-Rynning, Christilla
Abstract: EU trade policy is in flux. This reflects various developments, chief among them: the deepening of the global trade liberalisation agenda, the EU's own constitutional recasting of the Common Commercial Policy, and the politicization of trade. The purpose of this special issue is to analyse the changing politics of trade in the EU, focusing on the EU FTAs with Korea, the US, Canada, and Japan. We propose to view the negotiations of these agreements through the lens of contentious market regulation . This approach takes the regulatory turn in trade seriously, and sheds light on its ramifications for the mobilisation of new actors and the involvement of parliaments in the politics of trade. After tracing the development of the new EU FTAs and discussing the specificity of the EU's approach to deepened liberalisation, the article presents the framework of contentious market regulation and the individual contributions to the special issue.